Quality Index of School Education by Multiplicative aggregation - Chakrabartty, Satyendra Nath (Papanda Publisher, 2024)
Quality school education depends on a host of factors like tangible learning outcomes, efficient governance, necessary infrastructure, equitable academic opportunities, etc. For evaluation of evidence-based policy making in the education sector, the Ministry of Human Development and NITI Aayog, Govt. of India developed School Education Quality Index (SEQI) and assessed performance of States and Union Territories of India. The paper describes methodologically sound measure of overall performance in school education (OPSCI), avoiding normalization/scaling, selection of weights and covers all chosen indicators to reflect overall improvement/decline of a State/country in current year with respect to base year. The proposed index considering multiplicative aggregation of the chosen indicators has wider applications, satisfies desired properties, facilitates construction of OPSCI for India, in addition to State-wise indices. Thus, it is possible to have inter-country comparisons and inter-region comparisons. OPSCI also helps in identification of critical indicators requiring managerial attentions, plotting path of overall progress across time by a State or a country, testing statistical hypothesis regarding equality of the index for two countries/States or equality of the index for a single country/State across time using conventional t-tests on the logarithms of the observations. OPSCI with theoretical advantages is recommended. Future studies suggested.